Contactless Torque Sensor Development - Hajdu, F.; Horváth, P. (Acta Technica Jaurinensis, 2011)
This paper presents the development of a contactless torque sensor, which operates on a new principle. The used method is based on the birefringence effect of optically anisotropic materials. Experiments made are similar to the reflective photoelasticity. Instead of conventional photoelastic coating a Perspex tube of thin wall thickness was used. When torque was applied, stress had arisen in the tube, which could be measured optically. The main goal of this study was to create a torque sensor, which could be used in industry too. The paper deals with the theoretical basics, it gives an overview of the development up to now, presents measurement results, shows possible practical realizations for small and large torques, and also proposes possibilities for further developments.